Study on Stability Reduction Characteristics of Earth and Rockfill Dams under Rapid Drawdown Using Fully Coupled Seepage-Stress Analysis - Yong Nam Ri; Un Chol Han; Ui Jun Jang; Dok Yong Jong; Chol Ung Kim (Advances in Civil Engineering)
It can be a great expense to examine individually the stability of earth and rockfill dams on rapid drawdown in civil engineering practice. The aim of this present work is to clarify the safe type on the rapid drawdown among the most common types of earth and rockfill dams and to introduce cheaply the types in dam design. First, a transient analysis of saturated-unsaturated seepage coupled with stress is carried out in the cross sections of typical earth and rockfill dams the during rapid drawdown, and the safety factors of the upstream slopes are determined by the shear strength reduction method. Then, the typical dams are compared for the stability characteristics so that designers can select the safe type of earth and rockfill dams on rapid drawdown. The obtained results show that the decreasing rate of safety factor in a central core dam is 0.72–0.85 times than one of the homogeneous dams and 0.17–0.40 times than one of the sloping upstream core dams so that it is more stable than other earth and rockfill dams during rapid drawdown.